More perfect than the moon - MacLachlan, Patricia (New York : Joanna Cotler Books, 2004)
Eight-year-old Cassie Witting is upset when she finds out that her mother, Sarah, is expecting a baby, but writing in the journal that belonged to her brother Caleb helps her sort out her feelings and understand that Sarah will always love her.
Sequel to: Caleb's story.
3.2
3-6
3-6
Wilson's Children
School Library Journal
Keywords: Babies -- Fiction; Mothers and daughters -- Fiction; Frontier and pioneer life -- Great Plains -- Fiction; Great Plains -- Fiction; Historical fiction; Infants -- Fiction; Mother-daughter relationship -- Fiction; Frontier and pioneer life -- Great Plains -- Fiction; Great Plains -- Fiction; Historical fiction